The Transformation of Surau from Traditional Education Centres to Modern Spiritual Development Institutions in Minangkabau - Putri Adona; Ahmad Deski; Daniel Alfaruqi; Iswantir M (FiTUA: JURNAL STUDI ISLAM, 2025)
The surau is a traditional Islamic educational institution that has a vital role in shaping the character and religious identity of the Minangkabau people. However, modernisation and social change have affected its continued function as an educational centre. This study aims to analyse the transformation of the surau from the classical period to the modern era, highlighting changes in its institutional structure, learning methods, and social function. The method used is a Systematic Literature Review with a qualitative-descriptive approach, which involves searching various scientific sources from books, articles, and local documents. The results show that the Surau has undergone a shift in role from a community-based informal educational institution to a centre for moral and spiritual guidance that is more adaptive to the times. Despite undergoing modernisation, Surau has retained its core values of simplicity, togetherness, and spirituality. These findings prove that Surau has high resilience in facing social changes without losing its identity. This research makes an important contribution to the development of local wisdom-based Islamic education by offering an integrative model between tradition and modernity.